2016
DOI: 10.1093/eurheartj/ehw128
|View full text |Cite|
|
Sign up to set email alerts
|

2016 ESC Guidelines for the diagnosis and treatment of acute and chronic heart failure

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
4,451
4
512

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13,221 publications
(5,363 citation statements)
references
References 665 publications
47
4,451
4
512
Order By: Relevance
“…Currently, LVEF is the gold standard for risk stratification of heart failure patients, and severe LVEF reduction is an indication for prophylactic ICD implantation 3, 4. However, LVEF reflects the global systolic function of the heart, and does not necessarily correlate with pathological changes in myocardium facilitating VT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, LVEF is the gold standard for risk stratification of heart failure patients, and severe LVEF reduction is an indication for prophylactic ICD implantation 3, 4. However, LVEF reflects the global systolic function of the heart, and does not necessarily correlate with pathological changes in myocardium facilitating VT.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulatory ECG, Holter recordings and exercise tests were performed at baseline in all patients. New York Heart Association (NYHA) classification was documented for each patient at the baseline according to ESC and AHA Heart Failure Guidelines: NYHA Class I: no limitation of physical activity; NYHA Class II: slight limitation of physical activity in which ordinary physical activity leads to fatigue, palpitation, dyspnoea, or anginal pain; the person is comfortable at rest; Class III: marked limitation of physical activity in which less‐than‐ordinary activity results in fatigue, palpitation, dyspnoea, or anginal pain; the person is comfortable at rest; Class IV: inability to carry on any physical activity without discomfort but also symptoms of heart failure or the anginal syndrome even at rest, with increased discomfort if any physical activity is undertaken 4, 26. Patients were followed up between 2003 and 2013.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, national and international guidelines and recommendations are required to extrapolate the beneficial impact of disease‐modifying therapies and leave a degree of the decision‐making in the hands of the clinicians 11, 12, 13, 14. It has been demonstrated that adherence to recommendations regarding prescription of disease‐modifying therapies is variable and is impacted by renal function in trial settings 2, 15, 16.…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary management of heart failure (HF) includes multidisciplinary structured follow‐up programmes that provide patient education, medical treatment optimization, psychosocial support, and improved access to care 1. Such strategies are designed to improve outcomes and reportedly reduce HF‐related hospitalization and mortality following hospital discharge 2.…”
Section: Introductionmentioning
confidence: 99%